(untitled) (Proceedings of the International Conference on Education, 2021)
Due to the SARS-CoV-2 pandemic, many changes can be observed in almost all life situations, perhaps most notably, in the educational sector. In this context, concepts of learning counselling must be given more attention. This research contribution examines the question of how collaborative online tools to support the teaching-learning processes in higher education and vocational schools can be utilized. The aim is to improve the existing learning environment. For this purpose, the frequency of the usage of tools such as tests and forums on an open-source online learning platform ILIAS™ was analysed and discussed. In addition, the Adobe Connect™ web meeting software to be used in online teaching scenarios was also included in our investigation to explore the exchange of participants via discussion forums or virtual classrooms. The research team carried out an online sampling survey of ILIAS™ users at one university and five vocational schools in Germany in June 2020. The survey included these measures: Single answers, multiple answers, questions of scale, and free text questions. The response rate at the university was 25.10 % and at the vocational schools 17.2%. The data were evaluated with the help of descriptive statistics to determine frequency distributions and mean value calculations. This contribution will lead to a discussion regarding the continued disclosure of the learning potentials about a useful combination of both tools ILIAS™ and Adobe Connect™. The results shown suggest that the development towards virtual teaching scenarios, which has become a necessity under the forced conditions of the lockdowns, has a tremendous effect on teaching and learning processes in terms of didactics tailored to different target groups and needs in and outside the classroom.